Impact of Trypanosoma cruzi on antimicrobial peptide gene expression and activity in the fat body and midgut of Rhodnius prolixus - Vieira, CS (Parasit Vectors, 2016)
BACKGROUND: Rhodnius prolixus is a major vector of Trypanosoma cruzi, the causative agent of Chagas disease in Latin America. In natural habitats, these insects are in contact with a variety of bacteria, fungi, virus and parasites that they acquire from both their environments and the blood of their hosts. Microorganism ingestion may trigger the synthesis of humoral immune factors, including antimicrobial peptides (AMPs). The objective of this study was to compare the expression levels of AMPs (defensins and prolixicin) in the different midgut compartments and the fat body of R. prolixus infected with different T. cruzi strains. The T. cruzi Dm 28c clone (TcI) successfully develops whereas Y strain (TcII) does not complete its life- cycle in R. prolixus. The relative AMP gene expressions were evaluated in the insect midgut and fat body infected on different days with the T. cruzi Dm 28c clone and the Y strain. The influence of the antibacterial activity on the intestinal microbiota was taken into account. METHODS: The presence of T. cruzi in the midgut of R. prolixus was analysed by optical microscope. The relative expression of the antimicrobial peptides encoding genes defensin (defA, defB, defC) and prolixicin (prol) was quantified by RT-qPCR. The antimicrobial activity of the AMPs against Staphylococcus aureus, Escherichia coli and Serratia marcescens were evaluated in vitro using turbidimetric tests with haemolymph, anterior and posterior midgut samples. Midgut bacteria were quantified using colony forming unit (CFU) assays and real time quantitative polymerase chain reaction (RT-qPCR). RESULTS: Our results showed that the infection of R. prolixus by the two different T. cruzi strains exhibited different temporal AMP induction profiles in the anterior and posterior midgut. Insects infected with T. cruzi Dm 28c exhibited an increase in defC and prol transcripts and a simultaneous reduction in the midgut cultivable bacteria population, Serratia marcescens and Rhodococcus rhodnii. In contrast, the T. cruzi Y strain neither induced AMP gene expression in the gut nor reduced the number of colony formation units in the anterior midgut. Beside the induction of a local immune response in the midgut after feeding R. prolixus with T. cruzi, a simultaneous systemic response was also detected in the fat body. CONCLUSIONS: R. prolixus AMP gene expressions and the cultivable midgut bacterial microbiota were modulated in distinct patterns, which depend on the T. cruzi genotype used for infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1398-4) contains supplementary material, which is available to authorized users.